Effect of angiotensin-converting enzyme inhibitors and angiotensin receptor blockers on the short-term prognosis of COVID-19 infection. (14th October 2021) - Esteban-Lucia, L; Zambrano Chacon, M A; Venegas Rodriguez, A M; Devesa-Arbiol, A; Gonzalez-Rodriguez, M; Maure-Blesa, L; Avila-Barahona, P; Pello-Lazaro, A M; Gonzalez-Lorenzo, O; Kallmeyer-Mayor, A M; Fernandez-Roblas, R; Villar-Alvarez, F; et al.
Abstract: Background: Questions emerged about safety renin-angiotensin system (RAS) inhibitors (angiotensin-converting enzyme (ACE) inhibitors and angiotensin-receptor blockers (ARBs)) in patients diagnosed with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Our objective was to evaluate the safety of this treatment in a Spanish cohort during 2020 pandemic. Methods: Observational study including all consecutive patients (≥40 years old) diagnosed with SARS-CoV-2 through PCR in the microbiology laboratory of our hospital, since March 2nd to 20th 2020. Clinical characteristics and drugs were recorded. Primary end-point (PE) was the combined of all-cause death or need for orotracheal intubation until 30 days of infection symptoms onset. To assess the effect of RAS inhibitors, we performed a double statistical approach, with multivariate logistic regression and propensity-score matching. Results: We included 704 patients (table). Median age was 61 years old (IQR 52.9–72.9); 52.7% were female. 34.7% and 12.6% had hypertension (HTA) and diabetes (DM) respectively. 92 patients (13.1%) and 87 patients (12.4%) were taking ACEI and ARB respectively. Baseline characteristics of both subgroups are shown in the table. Patients on RAS inhibitors treatment had a worse clinical profile: were older, more males and with higher prevalence of HTA, DM, dyslipemia, ischemic heart disease and heart failure. There were no differences in terms of respiratory nor neoplasic disease. After 30 days, 112 patients (15.9%) had died, 148 (21.4%) had died or had required invasive mechanical ventilation (PE); 390 patients (55.4%) had needed hospital admission. PE was reached in 33.3% patients under ACEI treatment (vs. 19.6% in control group, p=0.005) and in 41.9% patients under ARB treatment (vs. 18.5% in control group, p<0.001). In the analysis to estimate the effect of ACEI no differences between groups were found (OR 1.01 [0.55–1.85], p=0.973). Likewise, in terms of ARB treatment, there were no differences among both groups (OR 1.66 [0.91–3.03], p=0.097). Using a propensity-score approach 79 patients under ACEI treatment and 72 patients under ARB treatment were matched 1:1 with control patients (characteristics of matched population are described in the table) Logistic binary regression showed no significant differences on incidence of the PE in patients under ACEI treatment (OR 0.84, 95% CI [0.43–1.63], p=0.613) nor ARB treatment (OR 1.82, 95% CI [0.92–3.60], p=0.085). Nevertheless, there was a trend towards worse prognosis in ARB patients. Kaplan-Meier curves of survival free of death or need for mechanical ventilation in matched population (ACEI and ARB treatment) are shown in the figure. Conclusions: We have not found any correlation between the severity of the disease and the treatment with ACEI nor ARB. We do not recommend the withdrawal of these drugs during the current epidemic situation. Further studies are needed to assess this finding. FUNDunding Acknowledgement: Type of funding sources: None.